2018
DOI: 10.1116/1.5052702
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature (Ts/Tm < 0.1) epitaxial growth of HfN/MgO(001) via reactive HiPIMS with metal-ion synchronized substrate bias

Abstract: Low-temperature epitaxial growth of refractory transition-metal nitride thin films by means of physical vapor deposition has been a recurring theme in advanced thin-film technology for several years. In the present study, 150-nm-thick epitaxial HfN layers are grown on MgO(001) by reactive high-power impulse magnetron sputtering (HiPIMS) with no external substrate heating. Maximum film-growth temperatures T s due to plasma heating range from 70 to 150 °C, corresponding to T s /T m = 0.10-0.12 (in which T m is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 70 publications
1
16
0
Order By: Relevance
“…Increasing film porosity at higher substrate inclination angles α could be the main contribution to the loss of electrical conductivity in OAD HfN films due electron scattering at the column boundary [37]. At α = 5 • , ρ = 81 µΩ•cm, a value which is consistent with that of 70 µΩ•cm reported for polycrystalline HfN films on glass at 300 • C [38] or epitaxial HfN films on MgO(001) obtained by pulsed-laser deposition (44-75 µΩ•cm) [28] or by high-power impulse magnetron sputtering (70 µΩ•cm) [39]. Note that the resistivity of stoichiometric epitaxial HfN/MgO(001) layer grown at 650 • C is 14.2 µΩ•cm [40].…”
Section: Growth Morphologysupporting
confidence: 82%
“…Increasing film porosity at higher substrate inclination angles α could be the main contribution to the loss of electrical conductivity in OAD HfN films due electron scattering at the column boundary [37]. At α = 5 • , ρ = 81 µΩ•cm, a value which is consistent with that of 70 µΩ•cm reported for polycrystalline HfN films on glass at 300 • C [38] or epitaxial HfN films on MgO(001) obtained by pulsed-laser deposition (44-75 µΩ•cm) [28] or by high-power impulse magnetron sputtering (70 µΩ•cm) [39]. Note that the resistivity of stoichiometric epitaxial HfN/MgO(001) layer grown at 650 • C is 14.2 µΩ•cm [40].…”
Section: Growth Morphologysupporting
confidence: 82%
“…This major decrease in the ρ e value is primarily attributed to the improvement in the HfN x film microstructure, enabled by the impingement of ions with a larger mass and higher energy. Relevantly, Villamayor et al also recently showed that an increase in the mass of impinging ions by adopting Kr-N 2 plasma, instead of Ar-N 2 plasma, led to an improvement in the crystalline quality of the sputtered HfN x films [20]. The above results can be understood from the fact that the nature of ion-surface interaction depends on the extent of energy and momentum transfer.…”
Section: Discussionmentioning
confidence: 93%
“…Altogether, these excellent material properties lead to the very low ρ e of the HfN x films grown using Ar-H 2 plasma with energetic ion bombardment. Impinging ions during plasma processes are known to initiate several interactions with the growing films, for example, enhanced ad atom surface diffusion leading to decrease in the defect density; bulk lattice atom displacements resulting in a collision cascade; sputtering and ion-induced damage; ion implantation at higher ion energies [20,[43][44][45][46][47][48][49][50][51]. In regards to the material properties, Hultman et al and Petrov et al showed that energetic ions in a N 2 and Ar-N 2 plasma discharges respectively with |V bias | value in the range of 150 V-250 V can lead to annihilation of defects and reduction in nano-porosity in sputtered TiN films [52,53], and attributed the decrease in defect density to the near-surface and sub-surface diffusion processes [44,45].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations